2007
DOI: 10.1111/j.1540-5907.2007.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and the Evolving American Welfare State: Examining Policies in the U.S. States

Abstract: The inclusion of racial/ethnic minorities is often considered an important factor leading to a relatively limited American welfare system. However, given the federal nature of welfare eligibility rules and the states' role in determining benefit levels, few studies explicitly link questions of inclusion and benefit levels when explaining the evolution of American welfare policy. This study examines the relationship between inclusion and benefit levels by analyzing state policies related to the welfare reforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
153
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 30 publications
2
153
1
Order By: Relevance
“…Scholars have long associated high racial heterogeneity with low support for social welfare in a society (Banting and Kymlicka 2005;Gilens 2003;Habyarimana et al 2007;Hero and Preuhs 2007;Miguel 1999;Miguel and Gugerty 2005;Soss et al 2001;Wolfe and Klausen 1997). One consequence of increasing immigration rates over the past several decades is increasing racial, ethnic, or nationality heterogeneity, particularly as immigrant populations disperse beyond the typical gateway states.…”
Section: Previous Research: What Do We Know?mentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have long associated high racial heterogeneity with low support for social welfare in a society (Banting and Kymlicka 2005;Gilens 2003;Habyarimana et al 2007;Hero and Preuhs 2007;Miguel 1999;Miguel and Gugerty 2005;Soss et al 2001;Wolfe and Klausen 1997). One consequence of increasing immigration rates over the past several decades is increasing racial, ethnic, or nationality heterogeneity, particularly as immigrant populations disperse beyond the typical gateway states.…”
Section: Previous Research: What Do We Know?mentioning
confidence: 99%
“…The bulk of the research in the American states clearly links increasing racial heterogeneity (i.e., increasing black populations) with declining support for welfare programs (Banting and Kymlicka 2005;Gilens 2003;Habyarimana et al 2007;Hero and Preuhs 2007;Miguel 1999;Miguel and Gugerty 2005;Soss et al 2001;Wolfe and Klausen 1997). Using the American experience with race and welfare as a foundation, comparative scholars have begun to examine whether or not the increasing immigrant populations experienced by Europe during the 1990s and 2000s might lead to an erosion of support for welfare programs (Burgoon, Koster, and van Egmond 2010;Eger 2010;Hjerm and Schnabel 2012;Larsen 2011;Mau and Burkhardt 2009;Sumino 2013).…”
Section: Immigrant-driven Diversitymentioning
confidence: 99%
“…Hero and Preuhs (2007) examine data on welfare spending for all U.S. states in 1998 and find that states with larger noncitizen populations tend to provide smaller cash benefits in their welfare programs, and this effect is larger the more accessible the welfare programs are to immigrants. In the right panel of Figure 1 we plot changes in state public welfare expenditures per capita against changes in the immigrant population.…”
Section: The Fiscal Burden Of Public Servicesmentioning
confidence: 99%
“…Race and ethnicity theory is perhaps the most recognized framework for understanding how immigration influences the welfare state, according to which immigration increases diversity, erodes social solidarity and as a result should reduce public welfare spending (Borjas & Trejo, 1990;Hero & Preuhs, 2007;Nannestad, 2007;Agrawal, 2008;Hainmuller & Hiscox, 2010). In addition to the race/ethnicity theory, globalization compensation theory could also shed light on the discussion of immigration and welfare, which suggests that immigration could result in economic risks and increase the incentives for governments to spend more on welfare compensation.…”
Section: Immigration and Welfare Spending In The Usmentioning
confidence: 99%
“…So far, much of what we know about immigration and the American welfare state is limited by discussions surrounding race and ethnicity (for an example see Hero & Preuhs, 2007). Numerous previous studies have shown that higher proportions of racial minorities such as African Americans are associated with less generous welfare provisions at the state and community levels; an important reason is that white Americans' perception of blacks being overrepresented in the welfare system lowers their support for welfare (Quadagno, 1994;Gilens, 1996Gilens, , 1999Alesina & Glaeser, 2004).…”
mentioning
confidence: 99%